The effect of topical ascorbic acid on cutaneous healing - Adriane Viana de Souza; Juan Carlos Montano Pedroso; Renata Andrade Bitar; Daniela de Oliveira Vieira; Cainã Cardoso Eduardo; Fernando Oliveira de Carvalho Peixoto (Revista Brasileira de Cirurgia Plástica)
Introduction: The surgical wound has high levels of free radicals in response to skin damage, which raises the hypothesis of a possible benefit from using antioxidants in repairing these wounds, such as the topical application of ascorbic acid. However, recent research has found conflicting conclusions about this type of treatment. The objective is to evaluate the effect of topical ascorbic acid on skin healing through a scope review. Methods: The scope review was carried out in the Medline, Lilacs and Cochrane databases, with the descriptors: ascorbic acid, skin cream, and wound healing. Inclusion criteria were defined as randomized clinical trials, observational and systematic reviews, in humans, with a publication date of up to 5 years, in English, Portuguese or Spanish. The following were excluded: narrative reviews, dissertations, theses, editorials, in vitro and animal studies. Finally, the studies were classified using the GRADE methodology. Results: 83 studies were found, and six articles were selected after screening. The use of ascorbic acid in the concentration of 5 to 20% and its derivatives (0.075% to 9.55%) stood out. The outcomes presented a moderate GRADE quality: increased skin firmness and reduced redness, and high quality: improved hydration, elasticity, colorimetry of the stains and improved wound closure. Conclusion: Ascorbic acid promotes better skin elasticity, reduced erythema and better wound closure. Despite these strong indications, randomized clinical trials with a lower risk of measurement bias and greater casuistry are still necessary.